Morphology and Function of the Lamb Ileum following Preterm Birth - Flores, Tracey J.; Nguyen, Vivian B.; Widdop, Robert E.; Sutherland, Megan R.; Polglase, Graeme R.; Abud, Helen E.; Black, Mary Jane (Frontiers in Pediatrics, 2018)
Background: For infants born moderately/late preterm (32-37 weeks of gestation), immaturity of the intestine has the potential to impact both short- and long-term gastrointestinal function. The aim of this study conducted in sheep was to compare the morphology and smooth muscle contractility of the ileum in term and late preterm lambs. Materials and Methods: Lambs delivered preterm (132 days gestation; n=7) or term (147 days gestation; n=9) were milk-fed after birth and euthanased at 2 days of age. A segment of distal ileum was collected for analysis of the length and cellular composition of the villi and crypts, smooth muscle width and contractility, and mRNA expression of the cell markers KI67, LYZ, MUC2, SYP, CHGA, OLFM4, AXIN2, and LGR5. Results: There was no difference in the proportion of inflammatory, proliferating, apoptotic, enterocyte, or goblet cells between groups, but preterm lambs exhibited a significant upregulation of the stem cell marker LGR5 (p=0.01). Absolute villus height (term: 1,032 ± 147 µm, preterm: 651 ± 52 µm; p<0.0001) and crypt depth (term: 153 ± 11 µm, preterm: 133 ± 17 µm; p=0.01) were significantly shorter in the preterm ileums, with a trend (p=0.06) for a reduction in muscularis externa width. There was no difference between groups in the contractile response to acetylcholine, but peak contractility in response to bradykinin (p=0.02) and angiotensin II (p=0.03) was significantly greater in the preterm lambs. Conclusion: Findings demonstrate that the crypt-villus units are shorter in the ileum of late preterm offspring, but functionally mature with an equivalent cellular composition and normal contractile response to acetylcholine compared to term offspring. The exaggerated contractility to inflammatory mediators evident in the preterm ileum, however, may be of concern.